2016
DOI: 10.1186/s12877-016-0366-3
|View full text |Cite
|
Sign up to set email alerts
|

Lower-extremity resistance training on unstable surfaces improves proxies of muscle strength, power and balance in healthy older adults: a randomised control trial

Abstract: BackgroundIt is well documented that both balance and resistance training have the potential to mitigate intrinsic fall risk factors in older adults. However, knowledge about the effects of simultaneously executed balance and resistance training (i.e., resistance training conducted on unstable surfaces [URT]) on lower-extremity muscle strength, power and balance in older adults is insufficient. The objective of the present study was to compare the effects of machine-based stable resistance training (M-SRT) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 64 publications
4
39
3
2
Order By: Relevance
“…The decline in these outcomes may lead to increased susceptibility to adverse conditions that impair the well‐being and health of the older people; thus, interventions that mitigate these changes become critical. Here, we showed that both UST and ST were able to improve the dynamic balance in older adults, which agrees with a previous study that demonstrated positive effects of both ST with and without postural instability on balance (UST—+2.26; 95% CI, 0.83‐3.70; ST—+1.22; 95% CI, 0.19‐2.63) . These findings have marked clinical implications during aging, since the reduction of the balance components is an independent risk factor for falls, frailty, and other geriatric syndromes…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The decline in these outcomes may lead to increased susceptibility to adverse conditions that impair the well‐being and health of the older people; thus, interventions that mitigate these changes become critical. Here, we showed that both UST and ST were able to improve the dynamic balance in older adults, which agrees with a previous study that demonstrated positive effects of both ST with and without postural instability on balance (UST—+2.26; 95% CI, 0.83‐3.70; ST—+1.22; 95% CI, 0.19‐2.63) . These findings have marked clinical implications during aging, since the reduction of the balance components is an independent risk factor for falls, frailty, and other geriatric syndromes…”
Section: Discussionsupporting
confidence: 91%
“…Although in the literature there are no studies with a similar experimental design, we used, for the calculation of the sample size, the results of two studies that were relatively similar to the present study . In both studies, effect sizes greater than 0.39 were reported for balance and functional outcomes.…”
Section: Methodsmentioning
confidence: 92%
“…Our previous research advocates the feasibility and effectiveness of instability resistance training 17 . Feasibility (high compliance and no training-related drop outs) was confirmed by this study.…”
Section: Discussionmentioning
confidence: 99%
“…The planned activities improve the body's position in space, which is particularly disturbed in people after stroke [4]. The proper functioning of the nervous system depends on physical activity.…”
Section: Objective Of Researchmentioning
confidence: 99%